2012
DOI: 10.5194/cpd-8-5925-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mid-Holocene climate reconstruction for eastern South America

Abstract: The Mid-Holocene (6 ka BP) is a key period to the study of climate, since it presented lower than present incoming summer insolation in the Southern Hemisphere, and the opposite in the Northern Hemisphere. This happened due to a different than present configuration of the orbital parameters. To investigate the effects of insolation on the Mid-Holocene climate, some global and regional multiproxy palaeodata compilations have been elaborated. However, few global studies have focused on the Southern Hemisphere, a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 124 publications
2
25
1
1
Order By: Relevance
“…Within our study area, Behling and Safford (2010) reconstructed a wet and warm period at the end of the Young Dryas (YD) chronozone followed by a considerably drier and cooler period until the mid-Holocene (about 5640 cal BP), before the climatic conditions became increasingly wetter. This trend is also suggested by other studies in South and Southeast Brazil (Behling, 1998;Rodrigues Filho et al, 2002;Scheel-Ybert et al, 2003, Wang et al, 2007, Prado et al, 2013. Based on sedimentological studies in the Guapi-Macacu catchment, Kirchner et al (2015) suggest a medium to low-energy fluvial environment for the mid-to early late Holocene indicating relative geomorphic stability.…”
Section: Chronological Placement Of Yellowish-brown Colluvial Depositssupporting
confidence: 65%
“…Within our study area, Behling and Safford (2010) reconstructed a wet and warm period at the end of the Young Dryas (YD) chronozone followed by a considerably drier and cooler period until the mid-Holocene (about 5640 cal BP), before the climatic conditions became increasingly wetter. This trend is also suggested by other studies in South and Southeast Brazil (Behling, 1998;Rodrigues Filho et al, 2002;Scheel-Ybert et al, 2003, Wang et al, 2007, Prado et al, 2013. Based on sedimentological studies in the Guapi-Macacu catchment, Kirchner et al (2015) suggest a medium to low-energy fluvial environment for the mid-to early late Holocene indicating relative geomorphic stability.…”
Section: Chronological Placement Of Yellowish-brown Colluvial Depositssupporting
confidence: 65%
“…A previous study (i.e., Prado et al, 2013) suggested a mid-Holocene water deficit scenario in South-eastern of South America compared to the late Holocene one. Low mid-Holocene austral summer insolation caused a reduced land-sea temperature contrast and hence a weakened South American monsoon system circulation.…”
Section: Climatic Changesmentioning
confidence: 95%
“…Along the Equator rainfall made by SACZ is at a near-minimum in DecembereFebruary, while the wettest season occurs in April and May (Waliser and Jiang, 2014). 3 El Niño southern oscillation (ENSO): Is the main cause of interannual variability of the SACZ movement (Trenberth, 1997) and its warm phase or El Niño is responsible for rainfall decline during the wet season of northern South America (Marengo et al, 2012;Prado et al, 2013).…”
Section: Climatementioning
confidence: 99%
“…During the austral summer over South America, the rainy season encompasses nearly the entire tropical area of the South American continent that lead to a latitudinally and longitudinally broad ITCZ (Waliser and Jiang, 2014). 2 South Atlantic convergence zone (SACZ): The SACZ is defined as a northwestesoutheast-oriented cloud band that is responsible for moisture transfer from the Amazon region to central and southeastern Brazil (Prado et al, 2013). Along the Equator rainfall made by SACZ is at a near-minimum in DecembereFebruary, while the wettest season occurs in April and May (Waliser and Jiang, 2014).…”
Section: Climatementioning
confidence: 99%